2014
DOI: 10.4025/actascibiolsci.v36i4.21482
|View full text |Cite
|
Sign up to set email alerts
|

<b>Blood pressure, heart rate and its autonomic modulation in malnourished rats at different ages

Abstract: Malnutrition is responsible for a number of alterations that occur in the organism, including alterations in the cardiovascular system. We hypothesize that long periods of malnutrition occurring after weaning may also be responsible for alterations in the cardiovascular system. Wistar rats were separated into the two following experimental groups: a labina ® diet-fed control group (CG) and a malnourished group (MG), fed a multi-deficient diet. Results showed that the mg presented significantly lower body weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Furthermore, Sant'Helena and colleagues demonstrated that rats fed a low‐protein (8%) diet from weaning to 9 months old presented resting tachycardia, which was also observed at the 3 (start of the analysis period), 4 and 5 months old (Sant'Helena et al . ). Therefore, resting tachycardia attributable to protein restriction is a well‐established condition that can last and starts within the first 35 days after weaning.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, Sant'Helena and colleagues demonstrated that rats fed a low‐protein (8%) diet from weaning to 9 months old presented resting tachycardia, which was also observed at the 3 (start of the analysis period), 4 and 5 months old (Sant'Helena et al . ). Therefore, resting tachycardia attributable to protein restriction is a well‐established condition that can last and starts within the first 35 days after weaning.…”
Section: Discussionmentioning
confidence: 97%